(untitled) (Research, Society and Development, 2020)
In sports, the fact that an athlete reaches the desired success or not is the result of the interaction of several factors, be they physiological, psychosocial or any other. The Plyometric Training (TP) is a method widely used in preparation for sport because it is capable of developing and improving various physical abilities required by the most varied sports modalities. Thus, the objective of this research was to analyze the information about the efficiency of the TP on the various physical abilities used within the Martial Arts and to carry out an integrative review, gathering articles of authors relevant to the subject. This research was characterized as an integrative review, which is defined as being able to gather and synthesize existing knowledge about a subject to incorporate it into the results of meaningful studies in practice. The articles were surveyed in the databases indexed in the Portal of Periodicals of the Coordination of Improvement of Higher Level Personnel, being selected studies published between the years 2007 and 2017. After the articles were collected, it was possible to find a total of 955 studies and, after analysis of the titles, 23 studies were chosen to be analyzed in their entirety. After this analysis only five were used for the preparation of this review. It has been seen that, through the TP aimed at Martial Arts modalities, the authors found good results for several physical abilities, among them are Strength, Speed, Power, Anaerobic Resistance, Coordination and Agility, these being fundamental within the modalities discussed here. Thus, the efficiency of the TP is concluded for the development and improvement of several physical capacities required in the MA, but it is also noticed that other physical capacities, such as flexibility, that were not mentioned in the studies.